Optimization of agropolitan tourism village for ornamental plants based on the concept of Tri Hita Karana - Mahendra, I Wayan Eka; Parmithi, Ni Nyoman; Agustien, Sri (Universitas Muhammadiyah Magelang, 2021)
The development of tourist villages, especially cultural tourism, is currently being intensified by the government through the Ministry of Tourism and Creative Economy (Kemenparekraf). Cultural tourism in Bali cannot be separated from the philosophy of Hinduism, one of which is Tri Hita Karana. Through the ornamental plant farmer group Guna Sari, the people of Petiga Village have developed plant agropolitan tourism based on tri hita karana, but it has not been managed optimally due to several obstacles. Among them are the unavailability of local tour guides and the weak ability of information technology in managing village webs for online promotion. Through training and mentoring, members of the Guna Sari ornamental plant farmer group were given English language training as a local tour guide, as well as computer training. The result is that members of the Guna Sari farmer group have mastered English for tourism and operate computers, which can be seen from the increase in evaluation results by 33.17% and 31.5%.